ROLE OF PURUN TIKUS IN VERTICAL SUBSURFACE FLOW CONSTRUCTED WETLAND IN TREATING MANGANESE (Mn) FROM COAL MINE DRAINAGE - Nopi Stiyati Prihatini; Indah Nirtha; Muhammad Sadiqul Iman (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2016)
Constructed wetland (CW) is one of the passive methods used to process coal mine drainage. In this study, we used vertical (VF) subsurface flow (SSF) constructed wetland (CW) with purun tikus (Eleocharis dulcis). The purpose of the study was to assess the role of purun tikus in increasing the efficiency of constructed wetland to remove Mn from Coal Mine Drainage. The constructed wetland operated under batch hydraulic loading regime. The results showed that the efficiency of the VF-SSFCW System without purun tikus was 15.53% and VF-SSFCW with purun tikus 78.94%.